Bowel ischemia as onset of COVID‐19 in otherwise asymptomatic patients with persistently negative swab. (8th October 2021) - Zamboni, Paolo; Bortolotti, Daria; Occhionorelli, Savino; Traina, Luca; Neri, Luca Maria; Rizzo, Roberta; Gafà, Roberta; Passaro, Angelina
Abstract: Background: Asymptomatic patients with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) can develop hypercoagulable conditions and acute vascular events. The objective of this study is to determine whether SARS‐CoV‐2 was present in resected specimens from patients with acute bowel ischemia, but asymptomatic for Coronavirus Disease 2019 (COVID‐19) and with persistently real‐time polymerase chain reaction negative pharyngeal swab. Methods: Three consecutive patients presented severe abdominal symptoms due to extensive ischemia and necrosis of the bowel, with co‐existent thrombosis of abdominal blood vessels. None had the usual manifestations of COVID‐19, and repeated pharyngeal swabs tested negative. They underwent emergency surgery with intestinal resection. Immunohistochemical testing for SARS‐CoV‐2 on resected tissue was performed. Results: All tested samples were strongly positive for SARS‐CoV‐2. Conclusions: This is the first case report in which patients with severe intestinal symptoms presented a marked SARS‐CoV‐2 positivity in the resected tissues, without any usual clinical manifestations of COVID‐19. These results suggest that the patients might be infected with SARS‐CoV‐2 presenting acute abdominal distress but without respiratory or constitutional symptoms. Abstract :